Eco-friendly Approach on Sand Dune Restoration in Micro-Tidal Beach - Ariffin, Effi Helmy; Sedrati, Mouncef; Ismailuddin, Aminah; Zainuddin, Siti Nur Hanani; Ramli, Muhammad Zahir; Siddiq, Ikhmal; Taslin, Puteri Nurfarah Adawiyah; Mokhtar, Mardiha (Coastal Education & Research Foundation (CERF), 2024)
Coastal erosion is a worldwide issue in which the absence of sand dunes could alter the landscape of beaches, especially those in micro-tidal environments. Practically, hard structures, such as revetments, is effective in mitigating erosion but do not protect well and can change the beach’s natural landscape and appeal. Therefore, an eco-friendly approach using wooden fence in a beach dune at a coast in Terengganu, Malaysia, can act as an alternative to control the erosion. This eco-friendly approach is known as E-Fence or Effective Sand Fences, which has proven to be effective in reducing the impact of erosion. In this research, the E-Fence was installed in a zigzag pattern parallel to the shoreline and placed within the Highest Astronomical Tide (HAT) and Mean Higher High Water (MHHW) water level. The effectiveness of the E-Fence in mitigating the erosion in the micro-tidal beach was identified through beach profile, sediment characteristics, and vegetation assessment. The beach profile were analyzed using the Profiler 3.2 XL program, revealing the sand dune accumulation at the back of the E-Fence, in comparison with and without the E-Fence which tends to be more eroded and steeper. Meanwhile, the GRADISTAT v8.0 was used to analyze the sediment characteristics, which showed the changing of particle size of the sand from very coarse to coarse sand. The installation of EFence is very affordable and effective, quick, easy to construct, and has a fast completion time while the vegetation line at the beach dune is well protected.